Emotional competence: A core competence in gerontological nursing in Iran. (24th September 2018) - Bahrami, Masoud; Purfarzad, Zahra; Keshvari, Mahrokh; Rafiei, Mohammad; Sivertsen, Nina
Abstract: Aim and objectives: Defining the components of emotional competence in caring for older people in Iranian hospitals. Background: People of older age are the largest recipients of healthcare services in hospitals. Thus, it is essential to establish what characteristics of emotional competence are required for nursing older people. Design: This qualitative descriptive‐exploratory study was conducted in Iran from September 2015 to April 2016. Methods: Semi‐structured interviews were conducted with 25 participants (nine nurses, 12 nurse managers, four clinical instructors), chosen by purposive and snowball sampling based on saturation. Data were analysed by content analysis method. Results: Qualitative content analysis identified two core categories and seven subcategories from the data: (a) Individual emotional competence with five subcategories of positive attitude, spiritual maturity, emotional self‐control, adherence to professional ethics and creativity and innovation, and (b) social emotional competence with two subcategories of relationship management and compassionate care. Conclusion: Emotional competence was identified as one of the main components of nursing skills when caring for older people. Gerontological nurses should demonstrate emotional competence in caring for older people and include a positive attitude, spiritual maturity, emotional self‐control, adherence to professional ethics, creativity in care, successful relationship management and compassionate care in their practice. Implications for practice: These findings can be used to guide development of emotional competencies for nursing older people.